2023
DOI: 10.1007/s00401-023-02637-2
|View full text |Cite
|
Sign up to set email alerts
|

Senescent fibro-adipogenic progenitors are potential drivers of pathology in inclusion body myositis

Christopher Nelke,
Christina B. Schroeter,
Lukas Theissen
et al.

Abstract: Inclusion body myositis (IBM) is unique across the spectrum of idiopathic inflammatory myopathies (IIM) due to its distinct clinical presentation and refractoriness to current treatment approaches. One explanation for this resistance may be the engagement of cell-autonomous mechanisms that sustain or promote disease progression of IBM independent of inflammatory activity. In this study, we focused on senescence of tissue-resident cells as potential driver of disease. For this purpose, we compared IBM patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…Figure B ). These findings underline that the sIBM disease process not only severely affects lower limb muscle fibre morphology in accordance with the previous reports [ 12 , 13 ], but also supports the findings in a recently published study by Nelke et al, that to our knowledge, is the first to reveal that the atrophic effect of the disease appears to be highly fibre type-specific, preferentially affecting fast-contracting type 2 myofibres [ 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…Figure B ). These findings underline that the sIBM disease process not only severely affects lower limb muscle fibre morphology in accordance with the previous reports [ 12 , 13 ], but also supports the findings in a recently published study by Nelke et al, that to our knowledge, is the first to reveal that the atrophic effect of the disease appears to be highly fibre type-specific, preferentially affecting fast-contracting type 2 myofibres [ 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…Giuliani and colleagues noted that FAPs expressing high levels of sca-1 exhibited a stronger inclination towards adipogenic differentiation in vitro. These cells also displayed increased sensitivity to fibrotic stimuli, resulting in elevated expression of col1 and tissue inhibitor of metalloproteinase1 (TIMP1) [ 64 ]. Malecova et al identified two distinct FAPs subpopulations characterized by the expression of TEK receptor tyrosine kinase (Tie2) and vascular cell adhesion molecule 1 (Vcam1).…”
Section: Discussionmentioning
confidence: 99%
“…The biopsies were blinded for quantification with the group not possible to identify from the label. The scoring was performed in randomly distributed 10 high-power fields (HPF, based on the microscope used and the respective oculars ≙ 0.16 mm 2 ), as previously described [ 12 ].…”
Section: Methodsmentioning
confidence: 99%